Fuzzy data analysis methodology for the assessment of value of information in the oil and gas industry. - Vilela, Martin; Oluyemi, Gbenga; Petrovski, Andrei (Institute of Electrical and Electronics Engineers (IEEE), 2018)
To manage uncertainty in reservoir development projects, the Value of Information is one of the main factors on which the decision is based to determine whether it is necessary to acquire additional data. However, subsurface data is not always precise and is characterized by a certain level of fuzziness. In this paper, a model is formulated to assess the Value of Information in the oil and gas industry in cases where the data proposed to be acquired is imprecise. The methodology is based on the use of fuzzy data modelling and analysis aimed at providing decision support for oil field developers. An oilfield from North Africa is used as a case study to show how the methodology works. This work shows how the analysis can be utilized to reach financial decisions on the necessity of additional data acquisition.
COMPLETED – Now available on IEEExplore 18/12/2018 LM – Still not on IEEE 8/10/2018, 21/8/2018, 30/7/2018 LM – Look in IEEE at end of Aug 6/7/2018 LM – Info via contact 4/5/2018 LM ADDITIONAL INFORMATION: Oluyemi, Gbenga ; Vilela, Martin ; Petrovski, Andrei – Panel B
Keywords: Fuzzy modelling; Value of information; Uncertainty and risks; Decision analysis and support; Oil and gas industry application